Ensuring Malaysian Food Security: Developing A Sustainable Aquaculture Framework of GAqP Compliant Fish Produce - Kamaruddin, Roslina; Soon, Jan Jan; Samah, Rozana; Rusmani, Rusmani (Universiti Utara Malaysia, 2022)
Aquaculture is, an important source of fish for human consumption, and sustainable production practice that comply with Malaysian Good Aquaculture Practice for aquaculture (GAqP) has recently become an important agenda in Malaysia. Driving forces behind the promotion of sustainable aquaculture are consumer awareness on sustainable aquaculture product. The objectives are to investigate the willingness of producers to produce GAqP-compliant farmed fish, consumer's preferences, awareness, willingness to pay for GAqP-compliant farmed fish and develop an eco-labeling and premium pricing framework. A contingent valuation approach was used to evaluate consumers’ WTP for fish welfare, using a single bounded dichotomous choice. To determine the factors that may influence consumers’ WTP for GAqP-Compliant farmed fish, the binomial logit model was used. Data were collected from an online survey of Malaysia consumers in June to July 2021 with the total sample size of 756. At each bid price level, more than 73% of respondents are willing to pay extra for GAqP-compliant farmed fish. Families with fewer households, those with higher incomes, and those who enjoy farmed fish are willing to pay a premium price. Consumers who are knowledgeable about aquaculture, practise green behaviour, aware of GAqP, and have a favourable perception of GAqP-compliant farmed fish are willing to pay extra.